Chapter 1 Re-theorizing religious conflict early Christianity to late antiquity and beyond - Mayer, Wendy (Taylor & Francis, 2018)
The nostalgic view that the classical polytheist world is one of religious tolerance and coexistence, whereas monotheism, which is exclusivist, is responsible for much of the religious violence perpetrated between the rise of Christianity and the end of pre-modern history. A dominant model that of the religious marketplace, is related, and similarly benchmarks the conversion of Constantine and focuses attention on Christianity and the religions of Greece and Rome. The emphasis on violence and the raising of questions about the role of the rhetoric of violence in relation to it brings us to one final influential perspective from which religious conflict in early Christianity and late antiquity has been addressed. Theorization of religious conflict in historical period has been criticized for its Christianity-centred focus. Christianity emerges in a pluri-religious urban society where it is in competition for converts.